Temporin L-derived peptide as a regulator of the acute inflammatory response in zymosan-induced peritonitis - Rosa Bellavita (Biomedicine & Pharmacotherapy, 2020)
Antimicrobial peptides (AMPs) are an ancient group of defense molecules distributed in nature being found in mammals, birds, amphibians, insects, plants, and microorganisms. They display antimicrobial as well as immunomodulatory properties. The aim of this study was to investigate, for the first time, the anti-inflammatory activities of two synthetic temporin-L analogues (here named peptide 1 and 2) by an in vivo model of inflammation caused by intraperitoneal sub-lethal dose of zymosan. Our results show that peptide 1 and 2 exert anti-inflammatory activity in vivo in response to zymosan-induce peritonitis. Simultaneous administration of 10 mg/kg of both temporins, with a sub-lethal dose of zymosan (500 mg/kg), significantly rescued mice from the classical hallmarks of inflammation, including leukocyte infiltration and synthesis of inflammatory mediators including IL-6, TNF-α and MCP-1. More importantly, flow cytometry analysis highlighted a selective modulation of infiltrating inflammatory monocytes (defined as B220−/GR1hi-F480hi/CD115+) after peptide 2 treatment. Our results and presented models offer the possibility to test, in a preclinical setting, the potential of temporin analogues as anti-inflammatory agents.